2018
DOI: 10.15294/dp.v12i2.13561
|View full text |Cite
|
Sign up to set email alerts
|

Think Pair Share (TPS) as Method to Improve Student’s Learning Motivation and Learning Achievement

Abstract: This research aims to find out the application of Think Pair Share (TPS) learning method in improving learning motivation and learning achievement in the subject of Introduction to Accounting I of the Accounting Study Program students of Politeknik Harapan Bersama. The Method of data collection in this study used observation method, test method, and documentation method. The research instruments used observation sheet, questionnaire and test question. This research used Class Action Research Design which is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
3
12
1
6
Order By: Relevance
“…The results of this study are in line with research conducted by Hetika, Farida, & Sari (2017) who apply TPS as a method for improving student learning motivation and learning achievement. The results showed that the application of TPS Learning (TPS) Method can improve Motivation and Learning Achievement.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are in line with research conducted by Hetika, Farida, & Sari (2017) who apply TPS as a method for improving student learning motivation and learning achievement. The results showed that the application of TPS Learning (TPS) Method can improve Motivation and Learning Achievement.…”
Section: Discussionsupporting
confidence: 88%
“…This learning model is also used to other disciplines to improve students' learning outcomes, such as computers [15], physics, chemistry, biology, and even in statistics [10] and mathematics [16]. In mathematics, TPS can also be applied in various fields study, such as geometry [17], probability [18], and to improve multiple aspects of instruction in mathematics, such as communication ability [19], learning motivation [16,20], and critical thinking [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the Enis et al (2012) study after applying the cooperative learning model of think pair share on the subject of optical devices showed collaboration and student learning outcomes had increased. Besides that the application of the think pair share learning model can increase motivation and learning achievement (Hetika et al, 2017).…”
Section: Planningmentioning
confidence: 99%